PELATIHAN AKUNTANSI LAPORAN KEUANGAN KEPADA SISWA SMP RICCI 1, JAKARTA - Wijoyo, Amin; Beatrice Tannessia Tandri; Adeline Putri Kurniawan (Jurnal Serina Abdimas, 2024)
Every economic entity requires accounting in their operations. Accounting is a continuous cycle that repeats each period, producing financial statements that meet quality standards. One of the important documents prepared by a company is the financial statement, which reflects the company’s performance and financial position during a specific accounting period. Financial statements include the income statement, statement of changes in equity, statement of financial position, cash flow statement, and notes to the financial statements. These reports provide information about the entity's financial condition and performance, which are useful for various parties, such as creditors and investors, in making economic decisions. Additionally, financial statements serve as a form of accountability for management regarding the resources entrusted to them. As part of the implementation of the Tri Dharma of Higher Education, this Community Service activity aims to benefit society, especially students of SMP Ricci 1, by enhancing their understanding of corporate financial statements. This training will focus on corporate financial statements and will take place over 80 minutes in a face-to-face session in August 2024. In this event, the PKM Untar team will start with an introduction to the material, followed by practice questions, and conclude with a Q&A session. It is expected that through this training, students will gain a better understanding of the importance of financial statements in a corporate context. ABSTRAK Setiap entitas ekonomi membutuhkan akuntansi dalam operasional mereka. Akuntansi adalah siklus berkelanjutan yang berulang setiap periode, menghasilkan laporan keuangan yang memenuhi standar kualitas. Salah satu dokumen penting yang dibuat perusahaan adalah laporan keuangan, yang menggambarkan kinerja dan posisi keuangan dalam satu periode akuntansi. Laporan keuangan mencakup laporan laba rugi, laporan perubahan modal atau ekuitas, laporan posisi keuangan, laporan arus kas, dan catatan atas laporan keuangan. Laporan ini memberikan informasi tentang kondisi keuangan dan kinerja entitas, yang bermanfaat bagi berbagai pihak seperti kreditor dan investor untuk pengambilan keputusan ekonomi. Selain itu, laporan keuangan juga merupakan bentuk pertanggungjawaban manajemen atas pengelolaan sumber daya yang dipercayakan kepada mereka. Sebagai bagian dari implementasi Tri Dharma Perguruan Tinggi, kegiatan Pengabdian Kepada Masyarakat ini bertujuan memberikan manfaat bagi masyarakat, terutama siswa SMP Ricci 1, agar lebih memahami laporan keuangan perusahaan. Pelatihan ini berfokus pada laporan keuangan perusahaan dan berlangsung selama 80 menit dalam satu sesi tatap muka pada Agustus 2024. Dalam kegiatan ini, tim PKM Untar akan memulai dengan pengenalan materi, dilanjutkan dengan latihan soal, dan diakhiri dengan sesi tanya jawab. Diharapkan melalui pelatihan ini, siswa dapat memahami dengan lebih baik pentingnya laporan keuangan dalam konteks perusahaan.